Computational and Medicinal Chemistry Approach to Explore the Pharmacological Potential of Naturally-Occurring Lactones - Tripathi, Nancy (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Pharmaceutical Engineering